2000
DOI: 10.1086/318139
|View full text |Cite
|
Sign up to set email alerts
|

Home Sampling versus Conventional Swab Sampling for Screening ofChlamydia trachomatisin Women: A Cluster‐Randomized 1‐Year Follow‐up Study

Abstract: We compared the efficacy of a screening program for urogenital Chlamydia trachomatis infections based on home sampling with that of a screening program based on conventional swab sampling performed at a physician's office. Female subjects, comprising students at 17 high schools in the county of Aarhus, Denmark, were divided into a study group (tested by home sampling) and a control group (tested in a physician's office). We assessed the number of new infections and the number of subjects who reported being tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
2
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(154 citation statements)
references
References 33 publications
3
137
2
12
Order By: Relevance
“…The use of SCVSs might also help to increase the acceptability of screening programs for women, given that recent studies have shown that these samples are highly acceptable and perform as well as, if not better than, FVU specimens and endocervical swabs (13,26). Evidence in support of screening based on home sampling with SCVSs in women and FVU specimens in men has been presented previously (2,20), and our findings support the choice of these specimen types. In addition, vaginal swab specimens are easier to handle during collection and transport and require fewer steps to process compared to FVU specimens.…”
Section: Fig 2 Organism Load In Matched Specimens From Men and Womesupporting
confidence: 75%
“…The use of SCVSs might also help to increase the acceptability of screening programs for women, given that recent studies have shown that these samples are highly acceptable and perform as well as, if not better than, FVU specimens and endocervical swabs (13,26). Evidence in support of screening based on home sampling with SCVSs in women and FVU specimens in men has been presented previously (2,20), and our findings support the choice of these specimen types. In addition, vaginal swab specimens are easier to handle during collection and transport and require fewer steps to process compared to FVU specimens.…”
Section: Fig 2 Organism Load In Matched Specimens From Men and Womesupporting
confidence: 75%
“…95% CI 0·22 to 0·83), 13,93 suggesting the overall result might overestimate the protective 319 effects of a screening test. Another completed cluster RCT will report on the association of up 320 to four rounds of chlamydia testing on the incidence of PID measured in hospitals and 321 primary care clinics.…”
mentioning
confidence: 99%
“…Equally, a randomised study with 9-year follow-up in women aged 21-23 years performed in Denmark found no differences between screened and non-screened women in the rates of PID and long-term risk of reproductive complications as the outcome (5). In contrast, two randomized trials comparing chlamydia screening in young women with a control group not invited for testing found a 50% reduction in PID over the subsequent year (64,82). Finally, in another randomised trial, limited evidence was observed suggesting that screening for chlamydia reduces PID rates: 10% of asymptomatic infected women not treated developed PID within a year, versus 2% of screened and treated women (63).…”
Section: Preventionmentioning
confidence: 95%